Meta Analisis Efektivitas Penggunaan Model Pembelajaran Problem Solving Terhadap Kemampuan Memecahkan Masalah Matematika SD 2020/2021 - Angga Ismail; Tego Prasetyo (Peneliti.net, 2021)
The purpose of this study was to determine the effectiveness of using the Problem Solving learning model on the ability to solve elementary school mathematics problems. The type of research used by the researcher in this study used the Meta-analysis method. This research will be carried out using the Problem Solving model. Researchers collect data by looking for journals with the same characteristics by using google scholar or scolaria. The results showed that the Problem Solving learning model was very efficient to use to improve the ability to solve mathematical problems in elementary schools.